Epidemiology of reinfections by SARS-CoV-2 variants during the third and fourth waves of the COVID-19 pandemic - Eduardo García-Moncada; Iliana Alejandra Cortés-Ortíz; María Fernanda Quijano-Soriano; Andrés Emmanuel Nolasco-Rojas; Sonia Chávez-Ocaña; Miguel Ángel Loyola-Cruz; Magnolia del Carmen Ramírez-Hernández; Claudia Camelia Calzada-Mendoza; Georgina Victoria-Acosta; Erika Gomez-Zamora; Juan Carlos Bravata-Alcántara; Juan Manuel Bello-López (Journal of Infection in Developing Countries)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic is a global health concern and has persisted through the emergence of variants that have caused subsequent waves of COVID-19 due to the high dispersion and contagiousness of the virus. The aim of this work was to analyze the epidemiology of the cases of reinfection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants during the third and fourth wave of the COVID-19 pandemic at the Hospital Juárez de México (HJM).